Oral cavity disorders in traditional, ethnic and original people communities (International Seven Journal of Multidisciplinary, 2024)
This chapter describes a worrying scenario and the territory of multidisciplinary health work in Brazil, a diverse country: the knowledge on the part of the dentist and the multidisciplinary team about the health of the black population corresponds to a demand in health, since this group has a predisposition to certain diseases, which if diagnosed early, will be possible to contribute to better therapeutic planning, predictability, and a favorable prognosis in certain clinical manifestations. However, such semiological methodological research may also contribute to the investigation and better understanding of oral cavity disorders that occur in members of traditional communities, in addition to displaced people (indigenous and gypsies), in an urban presence in Rio de Janeiro/Brazil. , envisioning better health outcomes for these vulnerable populations. Periodontal disease can be defined as a multifactorial chronic inflammatory process that affects the protective and supporting tissues of the teeth. Several factors related to this process are currently recognized, such as environmental, genetic, socioeconomic, systemic, ethnic factors and individual susceptibility of the host (very well covered technically by Semiology and repertorization). The manifestations of periodontal disease in people of African descent and the possible causal relationships that make them more susceptible (as described for sickle cell anemia) were presented, thus indicating the need for an individualized preventive approach to this population. Habits that are harmful to the health of the oral cavity were also listed. Finally, we emphasize the culminating point that was the meeting in the health space of the 7th ward of the Homeopathy Service of the Hospital Geral Santa Casa da Misericórdia in Rio de Janeiro, when it was possible to talk about the importance of interventions on habits that compromise the style of life and quality of life also contribute to the emergence of oral cavity neoplasms. The path of health promotion via multidisciplinary health education carried out jointly by professionals who are members of Homeopathy institutions in Rio de Janeiro stood out in relevance.